Low Varicella Zoster Virus Seroprevalence Among Young Children in the Democratic Republic of the Congo. Issue 2 (February 2018) - Doshi, Reena H.; Alfonso, Vivian H.; Mukadi, Patrick; Hoff, Nicole A.; Gerber, Sue; Bwaka, Ado; Higgins, Stephen G.; Sinai, Cyrus; Cowell, Brian; Ngoie Mwamba, Guillaume; Okitolonda, Emile; Muyembe-Tamfum, Jean-Jacques; et al.
Abstract : Background: Varicella zoster virus (VZV) causes both varicella (chickenpox) and herpes zoster (shingles) and is associated with significant global morbidity. Most epidemiological data on VZV come from high-income countries, and to date there are limited data on the burden of VZV in Africa. Methods: We assessed the seroprevalence of VZV antibodies among children in the Democratic Republic of Congo in collaboration with the 2013–2014 Demographic and Health Survey. Dried blood spot samples collected from children 6–59 months of age were run on Dynex™ Technologies Multiplier FLEX® chemiluminescent immunoassay platform to assess serologic response. Multivariate logistic regression was then used to determine risk factors for VZV seropositivity. Results: Serologic and survey data were matched for 7, 195 children 6–59 months of age, among whom 8% were positive and 2% indeterminate for VZV antibodies in weighted analyses. In multivariate analyses, the odds of seropositivity increased with increasing age, increasing socioeconomic status, mother's education level, rural residence, and province (South Kivu, North Kivu, Bandundu, Bas Congo had the highest odds of a positive test result compared with Kinshasa). Conclusion: Our data suggest that VZV is circulating in DRC, and seropositivity is low among children 6–59 months. Seropositivity increased with age and varied by other sociodemographic factors, such as geographic location. This study provides the first nationally representative estimates of VZV infection among children in the DRC.